Guidelines for the Use of Molecular Biological Methods to Detect Sexually Transmitted Pathogens in Cases of Suspected Sexual Abuse in Children - Hammerschlag, Margaret R. (2012)
Testing for sexually transmitted infections (STIs) in children presents a number of problems for the practitioner that are not usually faced when testing adults for the same infections. The identification of an STI in a child, in addition to medical implications, can have serious legal implications. The presence of an STI is often used to support the presence or allegations of sexual abuse and conversely, the identification of an STI in a child will prompt an investigation of possible abuse. The significance of the identification of a sexually transmitted agent in such children as evidence of possible child sexual abuse varies by pathogen. While culture has historically been used for the detection of STIs in cases of suspected abuse in children, the increasing use of nucleic acid amplification tests (NAATs) in adults and the increasing proliferation of second-generation tests with better sensitivity and specificity has made inroads into the use of such tests in children, especially for diagnostic and treatment purposes. Acceptance by the medicolegal system for sexual abuse cases is still controversial and more test cases will be necessary before definitive use becomes standard practice. In addition, if these assays ever become legally admissible in court, there will be recommendations that more than one NAAT assay be used in order to assure confirmation of the diagnostic result.